2022
DOI: 10.1093/rb/rbac003
|View full text |Cite
|
Sign up to set email alerts
|

Titanium alloy composited with dual-cytokine releasing polysaccharide hydrogel to enhance osseointegration via osteogenic and macrophage polarization signaling pathways

Abstract: Titanium alloy has been widely used in orthopedic surgeries as bone defect filling. However, the regeneration of high-quality new bones is limited due to the pro-inflammatory microenvironment around implants, resulting in a high occurrence rate of implant loosening or failure in osteological therapy. In this study, extracellular matrix (ECM)-mimetic polysaccharide hydrogel co-delivering BMP-2 and IL-4 was composited with 3D printed titanium alloy to promote the osseointegration and regulate macrophage response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 61 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…To simultaneously enhance the differentiation of MSCs to osteoblasts and induce the polarization of macrophages to the M2-type, there have been several studies on the co-administration of BMP-2 and immunomodulatory cytokines (IL-4) or metal ions (Zn 2+ ) on Ti implants. These dual-modified implants could create a favorable osteoimmune microenvironment by switching macrophages from the M1 to M2 phenotypes at the bone-implant interface and improve bone regeneration and osseointegration for successful implantation 50,51 . Interestingly, the results also showed the synergistic effect of IL-4 or Zn 2+ combined with BMP-2 (rhBMP-2 or BMP-2 peptide) on M2-type macrophage polarization.…”
Section: Bmp2pp Alleviates Ti-induced Osteolysis In Micementioning
confidence: 99%
See 1 more Smart Citation
“…To simultaneously enhance the differentiation of MSCs to osteoblasts and induce the polarization of macrophages to the M2-type, there have been several studies on the co-administration of BMP-2 and immunomodulatory cytokines (IL-4) or metal ions (Zn 2+ ) on Ti implants. These dual-modified implants could create a favorable osteoimmune microenvironment by switching macrophages from the M1 to M2 phenotypes at the bone-implant interface and improve bone regeneration and osseointegration for successful implantation 50,51 . Interestingly, the results also showed the synergistic effect of IL-4 or Zn 2+ combined with BMP-2 (rhBMP-2 or BMP-2 peptide) on M2-type macrophage polarization.…”
Section: Bmp2pp Alleviates Ti-induced Osteolysis In Micementioning
confidence: 99%
“…BMMs (1 × 10 4 cells/well, 96-well plate) were cultured in osteoclast induction medium (GM supplemented with 30 ng/mL M-CSF and 50 ng/mL RANKL, R&D Systems) with different concentrations of BMP2pp (25,50,100,200, 400 ng/mL) for 5 days. The cells were then stained for TRAP (Sigma-Aldrich, USA).…”
Section: Osteoclastic Differentiationmentioning
confidence: 99%
“…M o d i f i c a t i o n o f b i o m a t e r i a l s a s a s t r a t e g y t o immunomodulate the fracture microenvironment has also been recently explored. Applying a biomimetic polysaccharide hydrogel-metal scaffold composite loaded with IL-4 and BMP-2 within femoral defects in rats, Wang et al observed an increase in the number of M2 macrophages and in the proliferation and differentiation of skeletal progenitors into osteoblasts, which significantly improved bone regeneration (69). In another study, Xu et al (70) developed an intramedullary nail composed of a copper-containing stainless steel as a strategy to deliver copper ions at the injury site, as this ion had been previously shown to considerably induce M2 macrophage polarization in vitro (71).…”
Section: Perspectives For the Development Of Advanced Therapiesmentioning
confidence: 99%
“…The two phenotypes of macrophages work differently in regeneration of various tissues [ 447 ]. M2 macrophages enhance bone repairing via cytokine production whereas M1 macrophages work conversely [ 448 ]. For tumor treatment, M1 macrophages are important for antigen presentation, which helps the immune cells to attack tumor cells.…”
Section: Cell–biomaterials Interactionsmentioning
confidence: 99%